Characteristics of bacterial and fungal communities and their impact during cow manure and agroforestry biowaste co-composting. (15th December 2022) - He, Yan; Liu, Dong; He, Xinhua; Wang, Yanliang; Liu, Jianwei; Shi, Xiaofei; Chater, Caspar C.C.; Yu, Fuqiang
Abstract: Microbial communities and environmental conditions are both of great importance for efficient utilization of agroforestry resources. Nevertheless, knowledge about the role of soluble nutrients and enzymatic properties, and their inner links with microbial communities remain limited. This is especially the case for the co-composting of agricultural and forestry biowaste. Here, we investigate the succession of key microbes during co-composting (sawdust + cow manure, SA; straw + cow manure, ST), employing amplicon sequencing, enzyme assays, and physicochemical analyses. N-fixing bacteria ( Pseudomonas ) and C-degrading fungi ( Acaulium ) have been identified as dominant taxa during such co-composting. Although eight antibiotic resistance genes were found to persist during composting, pathogenic microbes declined with composting time. NO3 − -N content was screened as a determinant structuring the bacterial and fungal communities, with importance also shown for C-degrading enzymes such as cellulose, laccase, and peroxidase activity. These results identify the key microbial taxa and their main interactive environmental factors, which are potentially valuable for the development of a mixed microbial inoculant to accelerate the maturation of agroforestry biowastes composting. Graphical abstract: Image 1 Highlights: Cow manure co-composting reduced pathogenic microbia. Pseudomonas and Acaulium were dominant players in mediating compost maturation. NO3 − -N content was a key determinant of compost microbial community structure.